Pengaruh Makanan Dan Minuman Probiotik Terhadap Penanganan Diare Pada Anak : Tinjauan Sistematis - Marisa, Marisa; Hijratul, Disa; Firdaus, Zaskia Amirosa; Cicelia, Christara; Nur, Fatima; Firdaus, Ghina; Arfi, Alzikra (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: A study in Vietnam showed that consumption of probiotic beverages reduced the incidence of diarrhea in children from 7.9% to 4.9%, with OR = 0.60 (95% CI: 0.35–1.01; p = 0.068). The risk of diarrhea was also significantly reduced in the probiotic group (75.6%) compared to the placebo group (95.0%; p < 0.001). This indicates that probiotic beverages and foods significantly reduce the incidence of diarrhea in children.Methods: The databases used by the researchers were PubMed, Scopus, and Web of Science Database. The search and selection process was carried out using inclusion and exclusion criteria in accordance with PRISMA, resulting in 10 articles with the keywords (Probiotics OR food) AND diarrhea AND children.Result: A study in Vietnam showed that consumption of probiotic beverages reduced the incidence of diarrhea in children from 7.9% to 4.9%, with OR = 0.60 (95% CI: 0.35–1.01; p = 0.068). A study in the Congo using probiotic RUTF showed a reduction in the duration of diarrhea from 6.68 days to 4.11 days. The risk of diarrhea was also significantly reduced in the probiotic group (75.6%) compared to the placebo group (95.0%; p < 0.001). This indicates that probiotic beverages and foods significantly reduce the incidence of diarrhea in children.Conclusion : This systematic review concludes that probiotic foods and beverages are effective in treating diarrhea in children. Further research is needed to evaluate the effectiveness of traditional Indonesian foods containing probiotics, such as tempeh, tape, dadih, and others, in treating diarrhea in children.